An ultra-broadband polarization-independent perfect absorber for the solar spectrum. Issue 76 (19th August 2015) - He, Xunjun; Yan, Shitao; Lu, Guangjun; Zhang, Qinfei; Wu, Fengmin; Jiang, Jiuxing
<x xml:space="preserve">Abstract</x> We numerically investigated an ultra-broadband, polarization-insensitive, and wide-angle metamaterial absorber for harvesting solar energy.